Bullying Interrupted: Victimized Students in Remote Schooling During the COVID-19 Pandemic - Repo Juuso; Herkama Sanna; Salmivalli Christina (Springer Nature, 2022)
We investigated how the transition to remote schooling during the COVID-19 pandemic affected the rates of bullying victimization among students in primary and lower secondary education and analyzed how a specific group of students, namely previously victimized students experienced remote schooling. The 2-month school lockdown offered a unique setting to explore the association between increasing Internet use and cyberbullying and reflect on the overlap between traditional bullying and cyberbullying in a new context. The main sample (n = 34 771) consisted of 10–16-year-old Finnish students who responded to an online survey during the remote schooling period in spring 2020. The sample was supplemented with data from two previous surveys conducted in the same schools in 2019 (n = 43,216) and in 2017 (n = 24,727). The prevalence of bullying victimization decreased substantially in all grade levels during the school lockdown. Physical isolation and surge in students’ Internet use did not seem to lead to an increase in cyberbullying. Before-lockdown victimized students evaluated the time in remote schooling more positively than expected: they reported relatively high school liking and more teacher support than other students. The pre-existing gap in school adjustment between victimized and non-victimized students did not increase, but surprisingly, decreased. Our results highlight the notion that the main arena to fight bullying is within in-person interactions in schools.